Wave-absorbing composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202611230795.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-16
AI Technical Summary
[0002]随着微电子技术向小型化、高性能化和高集成度方向快速发展,微电子器件的电磁兼容性和散热性能成为关键技术挑战,吸波材料作为解决电磁干扰问题的重要手段,其性能优化对保障电子设备可靠运行具有重要意义,目前吸波材料主要分为磁性吸波材料和含碳系列吸波材料两大类,磁性吸波材料主要通过磁损耗机制吸收电磁波,但为获得良好吸波效果通常需要较高填料含量,导致材料内部界面热阻显著增大,散热性能严重恶化,含碳系列吸波材料虽具有较高导热性,但主要依赖单一电损耗机制,导致电磁波吸收频带较窄,且材料内部界面声子散射严重,限制了其在宽频场景下的应用效果
[0021] Therefore, through the synergistic effect of soft magnetic composite materials and piezoelectric materials, and the dual optimization of material composition and interface structure, the interfacial thermal resistance of the soft magnetic composite material is controlled at 1.2 mm in the 0.06 GHz-4 GHz bandwidth range. 2 With a strength below K/W, it effectively avoids problems such as local overheating and performance degradation caused by excessively high interfacial thermal resistance in the application of microwave absorbing composite materials. It not only significantly improves the interfacial bonding strength of soft magnetic composite materials, ensuring that the material does not detach from the interface during actual use, but also further improves the stability and service life of soft magnetic composite materials, giving them excellent microwave absorption performance, heat dissipation performance and structural stability.
Smart Images

Figure CN122931333A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of magnetic materials technology, and in particular to microwave absorbing composite materials, their preparation methods and applications. Background Technology
[0002] With the rapid development of microelectronics technology towards miniaturization, high performance, and high integration, the electromagnetic compatibility and heat dissipation performance of microelectronic devices have become key technological challenges. Absorbing materials, as an important means of solving electromagnetic interference problems, play a crucial role in ensuring the reliable operation of electronic devices. Currently, absorbing materials are mainly divided into two categories: magnetic absorbing materials and carbon-containing absorbing materials. Magnetic absorbing materials mainly absorb electromagnetic waves through magnetic loss mechanisms, but achieving good absorption usually requires a high filler content, leading to a significant increase in interfacial thermal resistance and severely deteriorated heat dissipation performance. While carbon-containing absorbing materials have high thermal conductivity, they mainly rely on a single electrical loss mechanism, resulting in a narrow electromagnetic wave absorption bandwidth and severe phonon scattering at the material's internal interfaces, limiting their application in broadband scenarios. Furthermore, absorbing composite materials made from magnetic and carbon-containing absorbing materials achieve absorption functions using single-sheet or simple composite structures. The thermal resistance problems generated between multiple interfaces in such structures are particularly prominent, which is detrimental to their application in highly integrated electronic systems. Therefore, there is an urgent need to develop an absorbing composite material that combines excellent heat dissipation and absorption performance. Summary of the Invention
[0003] Therefore, it is necessary to provide a microwave absorbing composite material, its preparation method and application, which has both excellent heat dissipation and microwave absorption properties, in order to address the above-mentioned technical problems.
[0004] This application discloses a microwave absorbing composite material, comprising a soft magnetic composite material and a piezoelectric material dispersed in a substrate, wherein the soft magnetic composite material comprises alloy particles and a dielectric coating layer covering the surface of the alloy particles, and the mass ratio of the soft magnetic composite material to the piezoelectric material is 95:5-85:15.
[0005] In one embodiment, the dielectric coating layer is made of at least one of TiO2, SiO2, or Al2O3.
[0006] In one embodiment, the ratio of the standard deviation of the dielectric coating thickness to the average thickness is less than 10%.
[0007] In one embodiment, the mass ratio of the alloy particles to the dielectric coating layer is 4:1 to 9:1.
[0008] In one embodiment, an AlN layer is further stacked between the alloy particles and the dielectric coating layer, and the thickness of the AlN layer is less than or equal to 0.3 μm.
[0009] In one embodiment, the alloy particles are selected from at least one of FeCoNi alloy, FeNiMo, or FeSiAl. When the alloy particles are selected from FeCoNi alloy, the molar ratio of Fe, Co, and Ni is (0.9-1.1):(0.9-1.1):(0.9-1.1).
[0010] And / or, the particle size of the alloy particles is 10nm-500nm.
[0011] In one embodiment, the soft magnetic composite material has a mass fraction of 30%-60% in the microwave absorbing composite material.
[0012] In one embodiment, the piezoelectric material is selected from at least one of lead zirconate titanate nanowires, barium titanate nanoparticles, or polyvinylidene fluoride.
[0013] And / or, the material of the substrate is selected from epoxy resin, polyurethane or silicone rubber.
[0014] This application discloses a method for preparing the microwave absorbing composite material as described above, comprising the following steps:
[0015] Prepare the raw materials according to the formula of alloy particles, and then perform hydrogen plasma treatment, ball milling treatment and annealing treatment in sequence to obtain alloy particles.
[0016] A dielectric coating layer is formed on the surface of the alloy particles to obtain a soft magnetic composite material.
[0017] The soft magnetic composite material is mixed with the piezoelectric material to obtain a microwave absorbing composite material.
[0018] This application discloses the application of the microwave absorbing composite material as described above in electronic devices.
[0019] In the microwave absorbing composite material disclosed in this application, firstly, the alloy particles in the soft magnetic composite material provide magnetic loss, and the dielectric coating layer provides dielectric loss. The two work synergistically to form a magnetic-dielectric synergistic loss effect, achieving excellent broadband microwave absorption performance with a relatively low filler loading. Simultaneously, the dielectric coating layer provides a low-impedance path between materials, reducing phonon scattering and increasing the phonon mean free path from 0.5 μm to 1.2 μm, successfully controlling the interfacial thermal resistance to 8.7 mm. 2 Within K / W.
[0020] Secondly, the piezoelectric material surrounding the soft magnetic composite material can be activated by thermal expansion strain, generating a local piezoelectric polarization field. This polarization field preferentially plays a role in the area where heat accumulation and charge accumulation are most severe, strongly dispersing interface charge, effectively enhancing the interface charge dissipation capability, breaking the vicious cycle of "charge accumulation - increased thermal resistance - heat accumulation", preventing hot spot temperature runaway, improving the problem of uneven heat dissipation in traditional microwave absorbing and heat dissipation materials, avoiding the adverse effects of local overheating on performance, successfully overcoming the problem of conflict between microwave absorption and heat dissipation performance in existing technologies, and is suitable for electromagnetic protection and thermal management scenarios of high-frequency electronic equipment.
[0021] Therefore, through the synergistic effect of soft magnetic composite materials and piezoelectric materials, and the dual optimization of material composition and interface structure, the interfacial thermal resistance of the soft magnetic composite material is controlled at 1.2 mm in the 0.06 GHz-4 GHz bandwidth range. 2 With a strength below K / W, it effectively avoids problems such as local overheating and performance degradation caused by excessively high interfacial thermal resistance in the application of microwave absorbing composite materials. It not only significantly improves the interfacial bonding strength of soft magnetic composite materials, ensuring that the material does not detach from the interface during actual use, but also further improves the stability and service life of soft magnetic composite materials, giving them excellent microwave absorption performance, heat dissipation performance and structural stability. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the conventional technology, the drawings used in the description of the embodiments or the conventional technology will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 The image shows a scanning electron microscope (SEM) image of the microwave absorbing composite material prepared in Example 1.
[0024] Figure 2 The curve showing the relationship between the interfacial thermal resistance of the microwave absorbing composite material prepared in Example 1 and frequency.
[0025] Figure 3 The curve shows the relationship between the insertion loss of the microwave absorbing composite material prepared in Example 1 and the frequency. Detailed Implementation
[0026] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0028] In this invention, numerical ranges are involved. Unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe features or characteristics, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0029] This application discloses a microwave absorbing composite material, comprising a soft magnetic composite material and a piezoelectric material dispersed in a substrate. The soft magnetic composite material comprises alloy particles and a dielectric coating layer covering the surface of the alloy particles. The mass ratio of the soft magnetic composite material to the piezoelectric material is 95:5-85:15, including but not limited to 95:5, 94:6, 93:7, 92:8, 91:9, 90:10, 89:11, 88:12, 87:13, 86:14 or 85:15.
[0030] It should be noted that when the mass ratio of the soft magnetic composite material to the piezoelectric material is greater than 95:5, the piezoelectric material content will be too low and the local piezoelectric polarization effect will be insufficient. When the mass ratio of the soft magnetic composite material to the piezoelectric material is less than 85:15, the relative content of the soft magnetic filler will be reduced and the magnetic loss capacity will be insufficient.
[0031] In the microwave absorbing composite material disclosed in this invention, firstly, the alloy particles in the soft magnetic composite material provide magnetic loss, and the dielectric coating layer provides dielectric loss. The two work synergistically to form a magnetic-dielectric synergistic loss effect, achieving excellent broadband microwave absorption performance with a relatively low filler loading. Simultaneously, the dielectric coating layer provides a low-impedance path between materials, reducing phonon scattering and increasing the phonon mean free path from 0.5 μm to 1.2 μm, successfully controlling the interfacial thermal resistance to 8.7 mm. 2 Within K / W.
[0032] In one embodiment, the dielectric coating layer is made of at least one of TiO2, SiO2, or Al2O3. Since TiO2 has a high dielectric constant and good thermal stability, it can effectively enhance interfacial polarization loss. At the same time, it has strong interfacial bonding with alloy particles, which is beneficial to reducing thermal resistance. Therefore, the dielectric coating layer is preferably made of TiO2.
[0033] In one embodiment, the ratio of the standard deviation of the dielectric coating thickness to the average thickness is less than 10%, thereby ensuring that the dielectric coating is continuously, uniformly and without defects coated on the surface of the alloy particles, thus achieving better low thermal resistance.
[0034] In one embodiment, the mass ratio of the alloy particles to the dielectric coating layer is 4:1 to 9:1, including but not limited to 4:1, 5:1, 6:1, 7:1, 8:1 or 9:1. Within the above mass ratio range, the synergistic effect of high magnetic loss, low interfacial thermal resistance and good impedance matching of the microwave absorbing composite material can be better guaranteed.
[0035] In one embodiment, the alloy particles are selected from at least one of FeCoNi alloy, FeNiMo, or FeSiAl. When the alloy particles are selected from FeCoNi alloy, the molar ratio of Fe, Co, and Ni is (0.9-1.1):(0.9-1.1):(0.9-1.1), including but not limited to 0.9:1.1:1.1, 1.1:0.9:1.1, 1.1:1.1:0.9, 0.9:0.9:1.0, 0.9:0.9:1.1, 0.9:1.0:0.9, 0.9:1.0:1.0, 0.9:1.0:1.1, 0.9:1.1:0.9, 0. 9:1.1:1.0, 1.0:0.9:0.9, 1.0:0.9:1.0, 1.0:0.9:1.1, 1.0:1.0:0.9, 1.0:1.0:1.0, 1.0:1.0:1.1, 1.0:1.1:0.9, 1.0:1.1:1.0, 1.0:1.1:1.1, 1.1:0.9:0.9, 1.1:0.9:1.0, 1.1:1.0:0.9, 1.1:1.0:1.0, 1.1:1.0:1.1 or 1.1:1.1:1.0; thereby better improving the magnetic loss capability of alloy particles and ensuring the broadband absorption performance of soft magnetic composite materials.
[0036] In one embodiment, the particle size of the alloy particles is 10nm-500nm, including but not limited to 10nm, 50nm, 100nm, 200nm, 300nm, 400nm or 500nm. Within the above particle size range, the matching of magnetic loss and dielectric loss can be optimized. If the particle size exceeds the above particle size range, it is easy to cause poor dispersibility, weaken the effect of the dielectric coating layer, and cause the thermal resistance to increase. If the particle size is lower than the above particle size range, it is easy to cause the magnetic properties of the alloy particles to decrease.
[0037] In one embodiment, the mass fraction of the soft magnetic composite material in the microwave absorbing composite material is 30%-60%, including but not limited to 30%, 35%, 40%, 45%, 50%, 55% or 60%. Within the above mass fraction range, an effective balance between microwave absorption and heat dissipation can be achieved. If the mass fraction exceeds the above range, it is easy to cause the material to become more brittle, less flexible, and difficult to disperse the filler, resulting in increased thermal resistance. If the mass fraction is lower than the above range, it is easy to cause insufficient microwave absorption performance, making it difficult to meet the requirements of wideband high absorption.
[0038] To enhance the bonding ability between the alloy particles and the dielectric coating layer, in one embodiment, an AlN layer is further stacked between the alloy particles and the dielectric coating layer in the soft magnetic composite material. Preferably, the thickness of the AlN layer is less than or equal to 0.3 μm.
[0039] Secondly, the piezoelectric material surrounding the soft magnetic composite material can be activated by thermal expansion strain, generating a local piezoelectric polarization field. This polarization field preferentially plays a role in the area where heat accumulation and charge accumulation are most severe, strongly dispersing interface charge, effectively enhancing the interface charge dissipation capability, breaking the vicious cycle of "charge accumulation - increased thermal resistance - heat accumulation", preventing hot spot temperature runaway, improving the problem of uneven heat dissipation in traditional microwave absorbing and heat dissipation materials, avoiding the adverse effects of local overheating on performance, successfully overcoming the problem of conflict between microwave absorption and heat dissipation performance in existing technologies, and is suitable for electromagnetic protection and thermal management scenarios of high-frequency electronic equipment.
[0040] In one embodiment, the piezoelectric material is selected from at least one of lead zirconate titanate nanowires, barium titanate nanoparticles, or polyvinylidene fluoride. Since lead zirconate titanate nanowires have the characteristic of high piezoelectric coefficient, it is preferred that the piezoelectric material is selected from lead zirconate titanate nanowires. More preferably, the lead zirconate titanate nanowires have an average diameter of 50 nm-200 nm and an average length of 1 μm-10 μm.
[0041] In one embodiment, the material of the substrate is selected from at least one of epoxy resin, polyurethane, or silicone rubber.
[0042] Therefore, through the synergistic effect of soft magnetic composite materials and piezoelectric materials, and the dual optimization of material composition and interface structure, the interfacial thermal resistance of the soft magnetic composite material is controlled at 1.2 mm in the 0.06 GHz-4 GHz bandwidth range. 2 With a strength below K / W, it effectively avoids problems such as local overheating and performance degradation caused by excessively high interfacial thermal resistance in the application of microwave absorbing composite materials. It not only significantly improves the interfacial bonding strength of soft magnetic composite materials, ensuring that the material does not detach from the interface during actual use, but also further improves the stability and service life of soft magnetic composite materials, giving them excellent microwave absorption performance, heat dissipation performance and structural stability.
[0043] This application also discloses a method for preparing the microwave absorbing composite material as described above, comprising the following steps:
[0044] S10: Prepare the raw materials according to the formula of alloy particles, and then perform hydrogen plasma treatment, ball milling treatment and annealing treatment in sequence to obtain alloy particles.
[0045] S20, a dielectric coating layer is formed on the surface of the alloy particles to obtain a soft magnetic composite material;
[0046] S30, the soft magnetic composite material is mixed with the piezoelectric material to obtain a microwave absorbing composite material.
[0047] In step S10, hydrogen plasma treatment can remove oxides from the surface of the raw materials and activate the surface of the particles.
[0048] In one embodiment, the hydrogen plasma pretreatment step uses a mixture of argon and hydrogen in a volume ratio of 8:1 to 10:1.
[0049] To enhance plasma uniformity and generate active sites on the raw material surface, thereby improving subsequent alloying efficiency, a pulsed gas intake system alternately switches between high-flow and low-flow modes every 20-40 minutes. In the high-flow mode, the flow rate of the mixed gas is 100-200 sccm, and in the low-flow mode, the flow rate of the mixed gas is 20-50 sccm.
[0050] In one embodiment, a plasma source consisting of high-frequency, medium-frequency, and low-frequency plasma sources is used in sequence. The high-frequency plasma source has a frequency of 12MHz-14MHz and a duration of 10min-20min, which can promote ionization. The medium-frequency plasma source has a frequency of 4MHz-6MHz and a duration of 15min-30min, which can maintain the ion state. The low-frequency plasma source has a frequency of 90kHz-110kHz and a duration of 30min-60min, which can suppress powder agglomeration.
[0051] In one embodiment, during the hydrogen plasma pretreatment process, the temperature is first maintained at 20°C-30°C for 1.5-2.5 hours, and then the temperature is increased to 70°C-90°C and maintained for 2-4 hours.
[0052] During the ball milling and annealing processes, the rotation speed is 300rpm-400rpm, the ball-to-material ratio is 10:1-20:1, the time is 0.5h-1h, the annealing temperature is 180℃-220℃, and the time is 0.8h-1.2h.
[0053] In step S20, there is no limitation on the way the dielectric coating layer is formed on the surface of the alloy particles. It can be formed by hydrothermal reaction using titanium chloride and a complexing agent as raw materials.
[0054] When the dielectric coating material is selected from TiO2, in one embodiment, the molecular formula of titanium chloride is TiCl4, and the complexing agent is selected from at least one of citric acid, ethylenediaminetetraacetic acid, or tartaric acid.
[0055] In one embodiment, during the hydrothermal reaction, the temperature is increased to 170°C-190°C at a rate of 4°C / min-6°C / min, and the reaction lasts for 5-7 hours.
[0056] In step S30, to make the soft magnetic composite material and the piezoelectric material more uniformly mixed, the soft magnetic composite material and the piezoelectric material are dispersed in N-methylpyrrolidone (NMP) or acetone solvent in proportion and ultrasonically dispersed for 30-60 minutes at a power of 300-500W and a frequency of 40kHz. Then, they are transferred to a planetary mixer and mechanically stirred at a speed of 1000-1500rpm for 2-4 hours. Finally, they are degassed by vacuum, cast or molded, and cured at 80-120℃ for 2-4 hours.
[0057] This application also discloses the application of the microwave absorbing composite material as described above in electronic devices.
[0058] The technical solution of the present invention will be further described below through specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating the present invention and should not be regarded as limiting the scope of the present invention. Unless otherwise specified, specific conditions in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used without specified manufacturers are all commercially available conventional products.
[0059] Example 1
[0060] First, FeCoNi alloy particles were prepared: Iron powder (99.9% purity), cobalt powder (99.5% purity), and nickel powder (99.5% purity) were mixed in an atomic ratio of 1:1:1. The mixed powder was then pretreated with hydrogen plasma using a dynamic gas mixture of argon and hydrogen in a 9:1 ratio, with high and low flow rates switched every 30 minutes via a pulsed gas inlet system. Simultaneously, a three-frequency alternating plasma source was used, mixing 13.56MHz high frequency, 5MHz medium frequency, and 100kHz low frequency. For the first two hours of plasma treatment, forced water cooling at 25℃ was maintained; for the next two hours, the temperature was allowed to rise to 80℃; and finally, rapid cooling to -10℃ was performed for the last 30 minutes, resulting in stable pretreated FeCoNi alloy particles with an average particle size of 200nm.
[0061] Subsequently, the powder was ground using Y2O3-stabilized zirconia grinding balls at a speed of 350 rpm and a ball-to-powder ratio of 15:1 for 45 minutes. The ball-milled powder was then annealed for 1 hour in an environment of 0.01 MPa low-pressure argon gas and 200°C. Finally, a 0.1% oxygen / argon mixed gas was introduced for surface passivation to form an oxide layer with an average thickness of 2.5 nm.
[0062] Next, atomic layer deposition (ALD) was performed to prepare a surface deposition film of the FeCo alloy using a trimethylaluminum / NH3 system. Trimethylaluminum was cooled to -20°C, and NH3 was dissociated into active groups of NH2 and H. Gradient deposition was then performed using multi-gradient temperature control. The treated trimethylaluminum / NH3 was controlled with a three-stage temperature gradient: 250°C for the first 10 cycles, 210°C for the middle 30 cycles, and 170°C for the final 10 cycles. Each cycle employed a process of 0.1 seconds of trimethylaluminum pulse, 3 seconds of nitrogen purging, 0.2 seconds of NH3 pulse, and 5 seconds of nitrogen purging. After deposition, 254 nm ultraviolet light at 20 mW / cm² was used for illumination. 2 Under intense irradiation and in a 10% ozone atmosphere, the material is annealed at 150°C for 30 minutes to remove residual carbon, ultimately forming FeCoNi alloy nanomaterials with an AlN deposition layer.
[0063] FeCoNi alloy nanomaterials with an AlN deposition layer were placed in a 0.1 mol / L TiCl4 solution at a mass-to-volume ratio of 1:40. The mixture was heated to 180℃ at a rate of 5℃ / min at room temperature and reacted for 6 hours. 0.01 mol / L citric acid was added to adjust the citric acid to titanium ion ratio to 1:15, and the mixture was magnetically stirred at 200 rpm to promote uniform coating of the TiO2 layer. After the reaction, the mixture was allowed to cool naturally, and the product was collected by centrifugation. It was washed three times with 0.05 mol / L dilute ammonia to remove chloride ions, dried under vacuum at 60℃ for 12 hours, and then annealed at 450℃ for 2 hours under a nitrogen atmosphere to obtain FeCoNi@TiO2 powder. The mass ratio of FeCoNi alloy nanomaterials to the TiO2 dielectric coating layer was 6.5:1.
[0064] A hydrothermal method was used to react lead acetate, zirconium oxychloride, and tetrabutyl titanate as precursors at 200°C for 24 hours under the action of strong alkali NaOH to form a one-dimensional nanostructure. After washing, drying, and calcination at 650°C, lead zirconate titanate nanowires were obtained.
[0065] Pre-prepared FeCoNi@TiO2 powder and lead zirconate titanate nanowires were co-dispersed in a polymer epoxy resin at a mass ratio of 9:1:10. The mixture was then ultrasonically dispersed in N-methylpyrrolidone (NMP) for 40 minutes, followed by mechanical stirring at 1200 rpm for 3 hours. After vacuum degassing, the mixture was cast and cured at 100°C for 3 hours, resulting in a microwave absorbing composite material with the lead zirconate titanate nanowires randomly dispersed around the FeCoNi@TiO2 powder. The scanning electron microscope image of the microwave absorbing composite material is shown below. Figure 1 As shown.
[0066] Comparative Example 1
[0067] Comparative Example 1 was carried out in accordance with Example 1, except that the FeCoNi alloy nanomaterial was not coated with an AlN deposition layer and a TiO2 layer, but was directly mixed with lead zirconate titanate nanowires.
[0068] Comparative Example 2
[0069] Comparative Example 2 was carried out in accordance with Example 1, except that only the surface of the FeCoNi alloy nanomaterial was coated with an AlN deposition layer and a TiO2 layer, and it was not mixed with lead zirconate titanate nanowires.
[0070] Comparative Example 3
[0071] Comparative Example 3 was carried out in accordance with Example 1, except that the mass ratio of FeCoNi@TiO2 powder to lead zirconate titanate nanowires was 98:2.
[0072] Comparative Example 4
[0073] Comparative Example 4 was carried out in accordance with Example 1, except that the mass ratio of FeCoNi@TiO2 powder to lead zirconate titanate nanowires was 80:20.
[0074] Test Example 1
[0075] The interfacial thermal resistance of the microwave absorbing composite materials prepared in Examples 1 and 1-4 within the 0.06-4 GHz bandwidth was tested. The specific test methods are shown below, and the test results are shown in Table 1. The unit of interfacial thermal resistance in Table 1 is mm. 2 The resistance of the absorbing composite material provided in Example 1 as a function of frequency (K / W) is shown in the following curve. Figure 2 As shown, the insertion loss of the absorbing composite material provided in Example 1 varies with frequency as follows: Figure 3 As shown, the absorbing composite material provided in Example 1 achieves an insertion loss of over 30 dB in the 0.06 GHz-4 GHz bandwidth range, combined with... Figure 2 and Figure 3 It can be seen that the microwave absorbing composite material provided in Example 1 has both excellent heat dissipation performance and microwave absorption performance.
[0076] Interfacial thermal resistance: A thin metal wire is formed on the surface of the microwave absorbing composite material as a heater and temperature sensor. Alternating current of different frequencies is passed through the metal wire in sequence. By measuring the frequency voltage signal caused by the change in resistance at both ends of the metal wire, the thermal diffusivity and thermal conductivity of the microwave absorbing composite material can be calculated, and then the interfacial thermal resistance can be calculated.
[0077] Table 1
[0078]
[0079] Example 2
[0080] Example 2 is carried out in accordance with Example 1, except that the ratio of the standard deviation of the dielectric coating thickness to the average thickness is greater than 10%, specifically 15%.
[0081] Example 3
[0082] Example 3 was carried out in accordance with Example 1, except that the mass ratio of the soft magnetic composite material to the piezoelectric material was 95:5.
[0083] Example 4
[0084] Example 4 was carried out in accordance with Example 1, except that the mass ratio of the soft magnetic composite material to the piezoelectric material was 85:15.
[0085] Example 5
[0086] Example 5 was carried out in accordance with Example 1, except that the mass ratio of alloy particles to dielectric coating was 4:1.
[0087] Example 6
[0088] Example 6 was carried out in accordance with Example 1, except that the mass ratio of alloy particles to dielectric coating was 9:1.
[0089] Example 7
[0090] Example 7 is carried out with reference to Example 1, except that the mass fraction of the soft magnetic composite material in the microwave absorbing composite material is 30%.
[0091] Example 8
[0092] Example 8 is carried out with reference to Example 1, except that the mass fraction of the soft magnetic composite material in the microwave absorbing composite material is 60%.
[0093] Test Example 2
[0094] Referring to Test Example 1, the interfacial thermal resistance of the microwave absorbing composite materials prepared in Examples 2-8 was tested in the bandwidth range of 0.06-4 GHz. The test results are shown in Table 2, where the unit of interfacial thermal resistance is mm. 2 ·K / W.
[0095] Table 2
[0096]
[0097] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0098] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A microwave absorbing composite material, characterized in that, The invention includes a soft magnetic composite material and a piezoelectric material dispersed in a substrate, wherein the soft magnetic composite material comprises alloy particles and a dielectric coating layer covering the surface of the alloy particles, and the mass ratio of the soft magnetic composite material to the piezoelectric material is 95:5-85:
15.
2. The microwave absorbing composite material according to claim 1, characterized in that, The dielectric coating material includes at least one of TiO2, SiO2, or Al2O3.
3. The microwave absorbing composite material according to claim 1, characterized in that, The ratio of the standard deviation of the dielectric coating thickness to the average thickness is less than 10%.
4. The microwave absorbing composite material according to claim 1, characterized in that, The mass ratio of the alloy particles to the dielectric coating layer is 4:1 to 9:
1.
5. The microwave absorbing composite material according to claim 1, characterized in that, An AlN layer is also stacked between the alloy particles and the dielectric coating layer, and the thickness of the AlN layer is less than or equal to 0.3 μm.
6. The microwave absorbing composite material according to any one of claims 1-5, characterized in that, The alloy particles are selected from at least one of FeCoNi alloy, FeNiMo or FeSiAl. When the alloy particles are selected from FeCoNi alloy, the molar ratio of Fe, Co and Ni is (0.9-1.1):(0.9-1.1):(0.9-1.1). And / or, the particle size of the alloy particles is 10nm-500nm.
7. The microwave absorbing composite material according to any one of claims 1-5, characterized in that, The soft magnetic composite material has a mass fraction of 30%-60% in the microwave absorbing composite material.
8. The microwave absorbing composite material according to any one of claims 1-4, characterized in that, The piezoelectric material is selected from at least one of lead zirconate titanate nanowires, barium titanate nanoparticles, or polyvinylidene fluoride. And / or, the material of the substrate is selected from epoxy resin, polyurethane or silicone rubber.
9. A method for preparing a microwave absorbing composite material as described in any one of claims 1-8, characterized in that, Includes the following steps: Prepare the raw materials according to the formula of alloy particles, and then perform hydrogen plasma treatment, ball milling treatment and annealing treatment in sequence to obtain alloy particles. A dielectric coating layer is formed on the surface of the alloy particles to obtain a soft magnetic composite material. The soft magnetic composite material is mixed with the piezoelectric material to obtain a microwave absorbing composite material.
10. The application of a microwave absorbing composite material as described in any one of claims 1-7 in electronic devices.